Selective ribosome profiling reveals the cotranslational chaperone action of trigger factor in vivo - Oh, Eugene; Becker, Annemarie; Sandıkcı, Arzu; Huber, Damon; Chaba, Rachna; Gloge, Felix; Nichols, Robert J.; Typas, Athanasios; Gross, Carol A.; Kramer, Günter; Weissman, Jonathan S.; Bukau, Bernd (Cell, 2011)
As nascent polypeptides exit ribosomes, they are engaged by a series of processing, targeting, and folding factors. Here, we present a selective ribosome profiling strategy that enables global monitoring of when these factors engage polypeptides in the complex cellular environment. Studies of the Escherichia coli chaperone trigger factor (TF) reveal that, though TF can interact with many polypeptides, β-barrel outer-membrane proteins are the most prominent substrates. Loss of TF leads to broad outer-membrane defects and premature, cotranslational protein translocation. Whereas in vitro studies suggested that TF is prebound to ribosomes waiting for polypeptides to emerge from the exit channel, we find that in vivo TF engages ribosomes only after ∼100 amino acids are translated. Moreover, excess TF interferes with cotranslational removal of the N-terminal formyl methionine. Our studies support a triaging model in which proper protein biogenesis relies on the fine-tuned, sequential engagement of processing, targeting, and folding factors. - PaperClip
Gesehen am 12.10.2022